PENGEMBANGAN INDIKATOR 4C’s YANG SELARAS DENGAN KURIKULUM 2013 PADA MATA PELAJARAN MATEMATIKA SMA/MA KELAS X SEMESTER 1 - Nurmaharani, Rika; Sunardi, Sunardi; Kurniati, Dian (Department of Mathematics Education , University of Jember, 2017)
Abstract. This research aims to produce valid, development for 4C’s indicator that adjusment to curiculum of 2013 at first semester of tenth grade SMA/MA. Research type which is used is Plomp’s development research model. Plomp’s development phases consists of 4 phase which are, initial investigation phase; designing phase; realisation/construction phase; test, evaluation, and revision phase. The development of this research is 4C's indicator which is in line with the 2013 curriculum in the mathematics subjects of SMA/MA class X semster 1 consisting of 3 chapters: linear equations and linear inequality one variable containing absolute value, SPLTV, and function. The instrument used is the validation of 4C's indicator that is aligned with the 2013 curriculum. The results of this development is validated by 5 validators, namely 2 math teachers MAN 1 Jember and 3 lecturers of Mathematics Education Studies Program, University of Jember. The results of the development of 4C's indicator has a coefficient of 3.86 results categorized good validity. Thus the development of 4C's indiator in line with the 2013 curriculum in the mathematics course of SMA/MA class X semester 1 has met the criteria of validity. Keyword: Plomp’s development, 4C's indicator, Curriculum 2013